Wear-resistant super-hydrophobic heat-insulating coating and preparation method thereof
By covering fluorosilane-modified HNTs/SiO2 composite aerogel on the surface of the resin layer, the problems of weak fragility and thermal insulation effect of traditional SiO2 aerogel in high temperature environments are solved, and wear resistance, superhydrophobicity and Highly insulated coating, suitable for a variety of application scenarios and simplifies the preparation process.
Patent Information
- Application Number
- CN202411586267.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing thermal insulation coatings are fragile and have poor wear resistance under high temperature environments. The traditional SiO2 aerogel has low strength and is difficult to maintain a porous structure, resulting in unsatisfactory thermal insulation effect. The existing preparation methods are complex and damage to the substrate.
Using HNTs/SiO2 composite aerogel, the hydrophobic modification of fluorosilane forms a coating that is wear-resistant, superhydrophobic and high heat insulation. It combines the resin layer to provide adhesion. It uses spin coating method or high atomization spray gun spray technology to The surface of the resin layer is covered with HNTs/SiO2 composite aerogel powder material.
Achieves wear resistance and superhydrophobicity in high temperature environments, while improving heat insulation, providing good adhesion and durability. It is suitable for building curtain walls, aerospace and other fields, and the preparation process is relatively simple and low-cost .
Smart Images

Figure CN119264773A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite materials, and in particular relates to a wear-resistant super-hydrophobic thermal insulation coating and a preparation method thereof. Background Art
[0002] In recent years, with the rapid development of modern industry, energy consumption has increased, and the problem of energy shortage has become increasingly prominent. Energy-saving and consumption-reducing materials have attracted more and more attention. Among them, the use of thermal insulation coatings is an effective way to save energy and reduce consumption. Thermal insulation coatings improve the working environment and reduce energy consumption by reducing the heat accumulation inside the object. At the same time, dust and rainfall in the outdoor environment not only affect the appearance of the thermal insulation coating but also reduce the use effect of the coating.
[0003] Many animals and plants in nature have evolved for tens of thousands of years, giving them tens of thousands of hydrophobic surfaces, such as the unique waterproof surface of lotus leaves in nature, and the legs of dragonflies that are not soaked in water. In this phenomenon, the surface with a static contact angle greater than 150° and a rolling angle less than 10° is called a superhydrophobic surface. In order for the coating to achieve this physical property, it not only requires a surface with a special microstructure but also a very low surface energy. However, most studies only achieve the hydrophobic effect by reducing the surface energy of the object, rather than achieving a superhydrophobic surface with low surface tension by designing the surface morphology. The Cassie-Baxter wetting model shows that the more pores the coating structure carries and the rougher the surface, the better the superhydrophobic effect. Traditional SiO 2 Aerogel has physical properties such as high porosity and large specific surface area, which can well meet the technical requirements of super-hydrophobic surface. However, on the other hand, traditional SiO 2 The structure of aerogel also determines its serious defects of low strength and high brittleness. Moreover, it is difficult to maintain the original porous structure of the matrix under continuous high temperature environment, making it difficult to be directly used as a durable thermal insulation coating material in high temperature environment.
[0004] The thermal insulation effect and preparation method of the coating also have more or less problems in the current research. In terms of thermal insulation effect, although the barrier type thermal insulation coating has abundant raw materials and simple preparation, it is affected by the thin thickness of the coating, and the thermal insulation effect of the coating is mostly not ideal. In terms of preparation method, there are many methods for preparing coatings at present, such as chemical etching, stacking deposition, potential electrochemical deposition, plasma and laser treatment, oxidation, electrospinning, etc. These methods all have certain defects, such as: expensive processing equipment, complex process, damage to the substrate itself, poor adhesion and other defects. Therefore, it is urgent to seek a super hydrophobic coating material with good thermal insulation effect, wear resistance and strong adhesion. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a wear-resistant super hydrophobic thermal insulation coating and a preparation method thereof, using halloysite nanotubes (HNTs) / SiO 2 Composite aerogel not only overcomes the traditional SiO 2 The defects of aerogel, such as low strength and high brittleness, can further enhance the thermal insulation effect of the coating. At the same time, the resulting super-hydrophobic coating also has super wear resistance and adhesion.
[0006] In order to achieve the above purpose, the technical solutions adopted are as follows:
[0007] A wear-resistant super-hydrophobic thermal insulation coating material, comprising a resin layer coated on the surface of a substrate and HNTs / SiO2 coated on the surface of the resin layer. 2 Composite aerogel composition, the HNTs / SiO 2 The surface of the composite aerogel is hydrophobically modified by fluorosilane; the contact angle between the coating surface and water is 156-161°, and the rolling angle of water droplets on the surface is 3.2-6.4°. 2 The composite aerogel powder material is wear-resistant, super-hydrophobic and heat-insulating at the same time, and is firmly bonded to the resin layer, which provides sufficient adhesion.
[0008] According to the above scheme, the substrate includes inorganic non-metallic plate, metal plate and fabric. Specifically, the inorganic non-metallic plate includes plastic substrate, glass substrate, concrete, stone and other inorganic non-metallic substrates. Metal plate includes aluminum and its alloy substrate.
[0009] According to the above solution, the resin layer is made of epoxy resin or polyimide resin and has a thickness of 5-10 μm.
[0010] According to the above scheme, the fluorosilane is one of 1H,1H,2H,2H-perfluorooctyltrichlorosilane and 1H,1H,2H,2H-perfluorodecyltriethoxysilane.
[0011] According to the above scheme, the HNTs / SiO 2 The thickness of the composite aerogel powder material is 5-20 μm.
[0012] The preparation method of the above-mentioned wear-resistant super-hydrophobic thermal insulation coating material comprises the following steps:
[0013] 1) diluting epoxy resin or polyimide resin and its curing agent with a solvent to a mass concentration of 0.5-1%, applying them on a clean substrate surface and curing them to obtain a resin layer;
[0014] 2) HNTs / SiO 2The composite aerogel is ground and ultrasonically dispersed in anhydrous ethanol, and fluorosilane is added for hydrophobic modification to obtain a suspension; the suspension is evenly covered on the surface of the resin layer by spin coating or high-atomization spray gun spraying, and dried at 60°C to 80°C for 20 to 30 minutes to prepare a surface of HNTs / SiO 2 Wear-resistant superhydrophobic thermal insulation coating of composite aerogel.
[0015] According to the above scheme, the solvent in step 1) is ethanol or acetone.
[0016] According to the above scheme, step 2) the HNTs / SiO 2 The particle size of the composite aerogel after grinding is 5-20 μm.
[0017] According to the above scheme, step 2) the HNTs / SiO 2 The concentration of the composite aerogel in the suspension is 0.5wt% to 1wt%.
[0018] According to the above scheme, the rotation speed of the spin coating in step 2) is 1000-2000 rpm; during the spray coating process, the distance between the spray gun and the substrate is 20-30 cm.
[0019] According to the above scheme, the HNTs / SiO 2 The preparation method of the composite aerogel comprises the following steps:
[0020] 1) HNTs and isooctyltriethoxysilane are mixed and stirred in an organic solvent, and centrifugally dried to obtain modified HNTs;
[0021] 2) The modified HNTs were ultrasonically dispersed in ethanol to obtain a suspension with a concentration of 10 wt%, and tetraethyl orthosilicate, the suspension of HNTs, anhydrous ethanol and water were mixed in a mass ratio of (4-5):1:(5-7):2, and concentrated hydrochloric acid in a mass ratio of 3‰-4‰ was added dropwise, followed by an ethanolic ammonia solution, and the mixture was stirred at 35-50°C for 10-20 min to form a wet gel, which was then supercritically dried for 24-48 h to obtain HNTs / SiO 2 Composite aerogel.
[0022] According to the above scheme, the concentration of ethanol in the ammonia ethanol solution in step 2) is 2wt% to 3wt%.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention imitates the super hydrophobic surface structure in the biological world, and adopts the spin coating method or high atomization spray gun spraying method to coat the porous heat-insulating hydrophobic modified HNT S / SiO 2 The composite aerogel material is coated on the surface of the resin layer that is closely bonded to the substrate. The spherical SiO 2The particles are stacked together to form a dense protrusion structure to achieve a water-repellent effect. S With excellent mechanical properties, HNT S The mechanical properties of the composite aerogel prepared as a reinforcing fiber are greatly improved, making the coating material have good wear resistance. S Can further increase SiO 2 Aerogel's high porosity and specific surface area give it a more excellent thermal insulation effect, and it can be widely used in building curtain walls, aerospace, photovoltaic panels and other fields.
[0025] The present invention utilizes the principle that the more pores the coating structure carries, the rougher the surface, the better the super-hydrophobic effect in the Cassie-Baxter wetting model. Aerogel powder material with high porosity and large specific surface area is used as the surface layer of the coating. The raw material has the physical structure required for super-hydrophobicity and has excellent thermal insulation effect. In addition, the wear resistance of the coating is enhanced by adding halloysite nanofibers with high composite mechanical strength and stable performance. A resin material is used as the bottom layer of the coating, which is coated on the surface of the bottom layer by spraying or spin coating, and the resin layer is the surface layer HNT S / SiO 2 The composite aerogel powder provides strong adhesion, so that the coating has good durability. Therefore, it can be widely used in building curtain walls, aerospace, photovoltaic panels, etc. In addition, the preparation process of the present invention is relatively simple, the requirements for production equipment are relatively low, and it is a low-cost preparation method. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 :Pure SiO 2 Aerogel SEM image of aerogel.
[0027] Figure 2 :HNT S / SiO 2 Scanning electron microscope image of composite aerogel.
[0028] Figure 3 : Example 1: Super hydrophobic effect diagram of coating with gypsum board as substrate on different droplets.
[0029] Figure 4 : Example 2 shows the super-hydrophobic effect of the coating with filter paper as the substrate on different droplets.
[0030] Figure 5 : Example 3 shows the super-hydrophobic effect of the coating with glass sheet as the substrate on different droplets. DETAILED DESCRIPTION
[0031] The following examples further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention.
[0032] The specific embodiment provides a HNTs / SiO 2 Composite aerogel:
[0033] (1) 2.5 g HNTs were dispersed in 47.5 g ethanol solution and stirred for 2 h. 10 g isooctyltriethoxysilane was dissolved in 40 g N,N-dimethylformamide by mass, and the same mass of the mixture was added to the HNTs ethanol solution and magnetically stirred for 2 h in a water bath at 80 °C. The mixture was then centrifuged at 8000 rpm. The modified HNTs were obtained after drying.
[0034] (2) First, HNTs were ultrasonically emulsified for 10 min to prepare a 10 wt% HNTs ethanol suspension. 40 g of tetraethyl orthosilicate, HNTs ethanol suspension, anhydrous ethanol and water were mixed in a beaker at a mass ratio of 4:1:7:2 and poured into a three-necked flask. 0.45 g of concentrated hydrochloric acid was added dropwise to the flask, followed by 40 ml of ammonia ethanol solution. The mixture was stirred in a water bath at 35 °C for 10 min to form an HNTs / SiO 2 Composite wet gel, supercritical drying for 48h to prepare HNTs / SiO 2 Composite aerogel.
[0035] The pure SiO was imaged using a Philips Nanosem430 field emission scanning electron microscope. 2 Aerogel and HNTs / SiO 2 The microstructure of the composite aerogel was observed. Figure 1 , 2 As shown in the figure, it can be seen that the presence of HNTs nanofibers improves the microstructure of the composite aerogel. 2 Compared with aerogel, more connection points between nanoparticles are formed in the same space. 2 The network forms a porous three-dimensional network. After modification, HNTs nanotubes are 2 The composite aerogel has good dispersibility and is compatible with SiO 2 There are strong interactions between nanoparticles.
[0036] Example 1
[0037] The above HNT S / SiO 2 The composite aerogel was ground to a particle size of 5-20 μm, and 2 g was dispersed in 400 mL of anhydrous ethanol. The suspension was ultrasonically treated for 0.5 h, and then 6 mL of 17-fluorodecyltriethoxysilane (PFDTES) was added to the suspension under vigorous stirring, and then ultrasonicated for another 0.5 h to obtain hydrophobically modified HNT. S / SiO2 Composite aerogel suspension.
[0038] 5 g of epoxy resin and its curing agent were diluted with ethanol to a concentration of 1 wt %, and then coated on the surface of the gypsum board by spin coating at a speed of 1200 rpm for 10 s. The coating thickness after drying was 5 μm. S / SiO 2 The composite aerogel suspension was coated on the resin layer and spin-coated for 20 seconds, and then the gypsum board was dried at 80°C for 30 minutes to obtain a super-hydrophobic thermal insulation coating.
[0039] The super-hydrophobic effect of the coating of this embodiment on different droplets is shown in FIG. Figure 3 shown.
[0040] Example 2
[0041] The above HNT S / SiO 2 The composite aerogel was ground to a particle size of 5-20 μm, and 2 g was dispersed in 400 mL of anhydrous ethanol. The suspension was ultrasonically treated for 0.5 h, and then 6 mL of 17-fluorodecyltriethoxysilane (PFDTES) was added to the suspension under vigorous stirring, and then ultrasonicated for another 0.5 h to obtain hydrophobically modified HNT. S / SiO 2 Composite aerogel suspension.
[0042] 5 g of epoxy resin and its curing agent were diluted with acetone to a concentration of 0.8 wt %, and then coated on the filter paper surface by spin coating at a speed of 1000 rpm for 10 s. After drying, the coating thickness was 10 μm. Then, the hydrophobically modified HNT was coated by spin coating at a speed of 1000 rpm. S / SiO 2 The composite aerogel suspension was coated on the resin layer and spin-coated for 20 seconds, and then the filter paper was dried at 80°C for 30 minutes to obtain a super-hydrophobic thermal insulation coating.
[0043] The super-hydrophobic effect of the coating of this embodiment on different droplets is shown in FIG. Figure 4 shown.
[0044] Example 3
[0045] The above HNT S / SiO 2The composite aerogel was ground to a particle size of 5-20 μm, and 2 g was dispersed in 400 mL of anhydrous ethanol. The suspension was ultrasonically treated for 0.5 h, and then 5 mL of 17-fluorodecyltriethoxysilane (PFDTES) was added to the suspension under vigorous stirring, and then ultrasonicated for another 0.5 h to obtain hydrophobically modified HNT. S / SiO 2 Composite aerogel suspension.
[0046] 5 g of epoxy resin was diluted with acetone to obtain a sol with a concentration of 0.6 wt %. The sol was coated on the surface of a glass sheet by spin coating at a speed of 1000 rpm for 10 seconds. The coating thickness after drying was 5 μm. HNT was sprayed S / SiO 2 The composite aerogel suspension was coated on a glass slide. During the spraying process, the distance between the spray gun and the substrate was 25 cm, the spraying amount was controlled at 10 mL / min, and then the glass slide was dried at 80°C for 25 minutes to obtain a super hydrophobic thermal insulation coating.
[0047] The super-hydrophobic effect of the coating of this embodiment on different droplets is shown in FIG. Figure 5 shown.
[0048] The hydrophobic performance of the wear-resistant super hydrophobic thermal insulation coating material obtained in Example 1-3 was tested by dropping liquids such as water, milk, rapeseed oil, glycerin, and coffee onto the coating surface (see Appendix Figure 3 , 4 , 5), all kinds of droplets on the surface of the material are quasi-spherical in shape, showing excellent super-hydrophobicity. The thermal insulation performance was tested, and the sample was placed face down on a 90°C constant temperature water surface. The surface temperature was tested by an infrared measuring instrument to test the temperature difference between the back temperature and the room temperature. The thermal insulation performance of the coating was tested using a TC3000E thermal conductivity measuring instrument. Finally, the surface of the wear-resistant super-hydrophobic thermal insulation coating material was rubbed by a friction and wear testing machine (sliding diameter of 5mm, load of 0.98N, sliding speed of 25mm / s) and the contact angle was tested. The results are summarized in Table 1.
[0049] Table 1
[0050]
[0051] Comparative Example 1
[0052] The HNTs / SiO 2The composite aerogel was ground to a particle size of 1-5 μm. 2 g was dispersed in 400 mL of anhydrous ethanol. The suspension was ultrasonically treated for 0.5 h, and then 6 mL of PFDTES heptafluorodecyl triethoxysilane was added to the suspension under vigorous stirring. The suspension was ultrasonically treated for another 0.5 h. The hydrophobically modified HNTs / SiO 2 The composite aerogel suspension was sprayed on a glass slide with an epoxy resin base layer, the distance between the spray gun and the substrate was 25 cm, the coating thickness was 40 μm, and the substrate was then dried at 80°C for 30 minutes.
[0053] The contact angle of the prepared coating with water is 152°, the rolling angle of water droplets on its surface is 7.4°, and the thermal conductivity is 0.12W / mK. S / SiO 2 The composite aerogel is ground too finely, which destroys the pores and skeleton in the structure, reduces the porosity, and makes it lose some of its function of preventing heat convection, resulting in a decrease in wettability and thermal insulation performance.
[0054] Comparative Example 2
[0055] Pure SiO 2 The aerogel was ground to a particle size of 5-20 μm. 2 g was dispersed in 400 mL of anhydrous ethanol. The suspension was ultrasonically treated for 0.5 h, and then 6 mL of PFDTES heptafluorodecyl triethoxysilane was added to the suspension under vigorous stirring. The suspension was ultrasonically treated for another 0.5 h. The hydrophobically modified HNTs / SiO 2 The composite aerogel suspension was sprayed on a glass slide with an epoxy resin base layer, the distance between the spray gun and the substrate was 25 cm, the coating thickness was 40 μm, and the substrate was then dried at 80°C for 30 minutes.
[0056] The contact angle of the prepared coating with water is 151°, the rolling angle of water droplets on its surface is 7.5°, and the thermal conductivity is 0.075W / mK. Under the premise of keeping the same grinding fineness as that in the embodiment, the thermal insulation performance and hydrophobicity of the coating are inferior to those in the embodiment. This is because pure SiO 2 Aerogel vs HNT S / SiO 2 The composite aerogel has single pores and low porosity, which leads to an increase in thermal conductivity. 2 The growth and accumulation on the surface of tubular halloysite increases the roughness of the aerogel, and the hydrophobic effect is better than that of pure SiO 2 Aerogel is good.
[0057] Comparative Example 3
[0058] The HNTs / SiO 2The composite aerogel was ground to a particle size of 20-50 μm. 2 g was dispersed in 400 mL of anhydrous ethanol. The suspension was ultrasonically treated for 0.5 h, and then 6 mL of PFDTES heptafluorodecyl triethoxysilane was added to the suspension under vigorous stirring. The suspension was ultrasonically treated for another 0.5 h. The hydrophobically modified HNTs / SiO 2 The composite aerogel suspension was sprayed on a glass slide with an epoxy resin base layer, the distance between the spray gun and the substrate was 25 cm, the coating thickness was 40 μm, and the substrate was then dried at 80°C for 30 minutes.
[0059] The contact angle of the prepared coating with water is 150°, the rolling angle of water droplets on its surface is 8.4°, and the thermal conductivity is 0.21W / mK. 2 The composite aerogel was ground too coarsely. Although the pores and skeleton in the structure were not destroyed, the particles were too large to bond well with the base epoxy resin. Some areas were blank, resulting in poor overall hydrophobicity and thermal insulation performance.
Claims
1. A wear-resistant super-hydrophobic thermal insulation coating material, characterized in that The invention is composed of a resin layer coated on the surface of a substrate and a HNTs / SiO2 composite aerogel covered on the surface of the resin layer, wherein the surface of the HNTs / SiO2 composite aerogel is hydrophobically modified by fluorosilane; the contact angle between the coating surface and water is 156-161°, and the rolling angle of water droplets on the surface is 3.2-6.4°.
2. The wear-resistant super hydrophobic thermal insulation coating material as claimed in claim 1, characterized in that The substrate includes inorganic non-metallic plates, metal plates and fabrics. Specifically, the inorganic non-metallic plates include plastic substrates, glass substrates, concrete and stone inorganic non-metallic substrates. Metal plates include aluminum and its alloy substrates.
3. The wear-resistant super hydrophobic thermal insulation coating material according to claim 1, characterized in that The resin layer is made of epoxy resin or polyimide resin and has a thickness of 5-10 μm.
4. The wear-resistant super hydrophobic thermal insulation coating material according to claim 1, characterized in that The fluorosilane is one of 1H,1H,2H,2H-perfluorooctyltrichlorosilane and 1H,1H,2H,2H-perfluorodecyltriethoxysilane.
5. The wear-resistant super hydrophobic thermal insulation coating material according to claim 1, characterized in that The thickness of the HNTs / SiO2 composite aerogel powder material covering the surface of the resin layer is 5-20 μm.
6. The method for preparing the wear-resistant super-hydrophobic thermal insulation coating material according to claim 1, characterized in that The following steps are involved: 1) diluting epoxy resin or polyimide resin and its curing agent with a solvent to a mass concentration of 0.5-1%, applying them on a clean substrate surface and curing them to obtain a resin layer; 2) Grinding the HNTs / SiO2 composite aerogel and ultrasonically dispersing it in anhydrous ethanol, adding fluorosilane for hydrophobic modification to obtain a suspension; uniformly covering the surface of the resin layer with the suspension by spin coating or spraying with a high-atomization spray gun, and drying at 60°C to 80°C for 20 to 30 minutes to prepare a wear-resistant super hydrophobic thermal insulation coating with HNTs / SiO2 composite aerogel on the surface.
7. The method for preparing the wear-resistant super-hydrophobic thermal insulation coating material according to claim 6, characterized in that Step 2) The concentration of the HNTs / SiO2 composite aerogel in the suspension is 0.5wt% to 1wt%.
8. The method for preparing the wear-resistant super-hydrophobic thermal insulation coating material according to claim 6, characterized in that Step 2) The rotation speed of the spin coating is 1000-2000 rpm; during the spray coating process, the distance between the spray gun and the substrate is 20-30 cm.
9. The method for preparing the wear-resistant super-hydrophobic thermal insulation coating material according to claim 6, characterized in that The preparation method of the HNTs / SiO2 composite aerogel comprises the following steps: 1) HNTs and isooctyltriethoxysilane are mixed and stirred in an organic solvent, and centrifugally dried to obtain modified HNTs; 2) The modified HNTs are ultrasonically dispersed in ethanol to obtain a suspension with a concentration of 10 wt%, and tetraethyl orthosilicate, HNTs suspension, anhydrous ethanol and water are mixed in a mass ratio of (4-5):1:(5-7):2, and concentrated hydrochloric acid in a mass ratio of 3‰-4‰ is added dropwise, followed by an ethanolic ammonia solution. After stirring at a temperature of 35-50°C for 10-20 minutes, a wet gel is formed, and supercritical drying is performed for 24-48 hours to obtain an HNTs / SiO2 composite aerogel.
10. The method for preparing the wear-resistant super-hydrophobic thermal insulation coating material according to claim 9, characterized in that Step 2) The concentration of ethanol in the ammonia ethanol solution is 2wt% to 3wt%.
Citation Information
Patent Citations
Wear-resistant and super-hydrophobic coating material and preparation method thereof
CN105802446A
Method for preparing durable super-amphiphobic coatings capable of being sprayed
CN106893454A
Preparation method of highly transparent wear-resistant superhydrophobic composite coating
CN107022279A
Application of aerogel based on silicon dioxide to thermal insulation material
CN107473762A
Novel fibrous clay silicon dioxide double-network aerogel and preparation method and application thereof
CN109574026A
Cited By
Aerogel-based heat-preservation, heat-insulation and waterproof composite coating material for building outer wall and preparation method thereof
CN119842297A
A temperature-difference freeze-thaw resistant multilayer hydrophobic-aerogel composite protective coating suitable for highland environment and a preparation method thereof
CN122809927A